Exploratory Study of Patients' Life Situation after a Stroke - Nunes, Henrique José Mendes (2015)
Background. Brain diseases are a major health issue in modern societies, leading to multiple losses and disruptions. Objective. Based on the question "Are stroke patients' quality of life and well-being also influenced by hospitalization and its duration and nature?", this study aimed to characterize the patients' life situation upon returning home, assess the illness and recovery process, and understand how stroke patients experience hospital stay and discharge. Methodology. Qualitative, descriptive, exploratory study, using semi-structured interviews with a nonprobability sample of recent stroke patients. Results: .....